2009
DOI: 10.1371/journal.pntd.0000434
|View full text |Cite
|
Sign up to set email alerts
|

Control of Pyrethroid-Resistant Chagas Disease Vectors with Entomopathogenic Fungi

Abstract: Background Triatoma infestans-mediated transmission of Tripanosoma cruzi, the causative agent of Chagas disease, remains as a major health issue in southern South America. Key factors of T. infestans prevalence in specific areas of the geographic Gran Chaco region—which extends through northern Argentina, Bolivia, and Paraguay—are both recurrent reinfestations after insecticide spraying and emerging pyrethroid-resistance over the past ten years. Among alternative control tools, the pathogenicity of entomopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
0
25

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(197 citation statements)
references
References 44 publications
7
153
0
25
Order By: Relevance
“…CYP52X1 displayed robust activity (Ͼ40 pmol/min/mg of protein) against lauric (C12:0), myristic, and 10-epoxysteric acids, 2-10 pmol/min/mg of protein of activity against C(9:0), C(16:0), C(18:1), and C(18:2), and ϳ 0.5 pmol/min/mg protein of activity against C18:0. These data indicate that the enzyme prefers the mid-range (possibly C 10 -11 , C [12][13][14] , and possibly C 15 ) saturated fatty acids. Intriguingly, the enzyme displayed better activity toward unsaturated and epoxy-C 18 fatty acids than toward the saturated C 18 fatty acid.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…CYP52X1 displayed robust activity (Ͼ40 pmol/min/mg of protein) against lauric (C12:0), myristic, and 10-epoxysteric acids, 2-10 pmol/min/mg of protein of activity against C(9:0), C(16:0), C(18:1), and C(18:2), and ϳ 0.5 pmol/min/mg protein of activity against C18:0. These data indicate that the enzyme prefers the mid-range (possibly C 10 -11 , C [12][13][14] , and possibly C 15 ) saturated fatty acids. Intriguingly, the enzyme displayed better activity toward unsaturated and epoxy-C 18 fatty acids than toward the saturated C 18 fatty acid.…”
Section: Discussionmentioning
confidence: 78%
“…Hydrocarbon assimilation plays a critical role in the ability of B. bassiana to infect certain insects, and alkane growth has been linked to increased virulence. Fungal cells grown on alkane-containing media displayed a 2-4-fold increase in mortality against the bean weevil Acanthoscelides obtectus when compared with cells grown on glucose (11), and derepression of the alkane pathway increased fungal virulence against insects that had developed resistance to chemical pesticides (12).…”
mentioning
confidence: 99%
“…Several isolates of the Ascomycetes Beauveria bassiana and Metarhizium anisopliae have been successfully used worldwide to control insects of both agricultural and medical importance (16)(17)(18)(19). B. bassiana is known as a broad host range arthropod pathogen capable of infecting a wide range of target hosts.…”
Section: Significancementioning
confidence: 99%
“…The authors found that recently hatched fi rst instar nymphs (1-3h old) were more vulnerable than older ones (24-36h old). Pedrini et al (65) used scanning electronic microscopy to show that Argentinean populations of T. infestans resistant to deltamethrin have thicker exoskeletons (32.1 ± 5.9μm) than susceptible populations (17.8 ± 5.4μm). Thicker cuticles enriched in hydrocarbons probably restrict deltamethrin penetration in resistant insects.…”
Section: Mechanisms Involved With Insecticide Resistance In Triatominaementioning
confidence: 99%